The Role of Indonesian Child Protection Commission (KPAI) in Legal Protection and Prevention of Child Trafficking Crimes - Alijana, Erma Hari (Indonesian Scientific Publication, 2024)
Human trafficking is a criminal phenomenon that significantly captures public attention, especially concerning child victims, which is most urgent. The aim of this research is to assess the role of the Indonesian Child Protection Commission (KPAI) in light of the increasing cases of child trafficking throughout 2024. This research method utilizes a normative juridical approach, whereby issues emerging in the field are examined through legal materials such as books or articles discussing human trafficking. The type of research conducted is qualitative research, utilizing a descriptive phenomenological approach. Human trafficking is categorized as a specific criminal offense and has been regulated in various legal provisions. These provisions encompass prohibitions and eradication measures as stipulated in legislation and the Convention on Human Trafficking. The research findings highlight efforts in preventing child trafficking crimes. Insufficient awareness among stakeholders both centrally and locally results in overlapping regulations regarding child trafficking crimes.